DGCR8-Mediated Production of Canonical Micrornas Is Critical for Regulatory T Cell Function and Stability - Jeker, Lukas T. (Public Library of Science, 2013)
Regulatory T cells (Treg) are integral for immune homeostasis. Here we demonstrate that canonical microRNAs (miRNAs) are required for Treg function because mice with DGCR8-deficient Treg cells spontaneously develop a scurfy-like disease. Using genetic lineage marking we show that absence of miRNAs leads to reduced FoxP3 expression in Treg cells in vivo. In vitro culture of purified DGCR8-deficient Treg leads to a loss of FoxP3 expression. We conclude that canonical miRNAs are essential to maintain stable FoxP3 expression and Treg function. Thus, signals interfering with miRNA homeostasis might contribute to autoimmune diseases.